The technology for chest 3D modeling aimed to increase the efficacy of diagnostic interventions in phthisiopulmonology - E. A. Filatova; S. N. Skornyakov; I. D. Medvinskiy; A. V. Bazhenov; V. A. Shibaev; N. A. Khlebnikov (Туберкулез и болезни лёгких)
The objective of the study: to increase efficacy of minimally invasive interventions in the diagnosis of limited disseminated and focal pulmonary lesions based on 3D-navigation modeling technologies.Subjects and methods. The informativeness of transbronchial lung biopsy (TBLB) with 3D navigation and traditional TBLB was compared in 50 patients in two groups. Group 1 included 20 patients with stage I and II sarcoidosis in whom a virtual-navigation map was drawn up using 3D modeling to accompany transbronchial lung biopsy. Group 2 consisted of 30 patients with stage I and II sarcoidosis who underwent standard TBLB. The informativeness of TBLB was evaluated by the results of histological tests of biopsy specimens.The developed software for positioning thoracoports was tested in 30 patients of two groups who were supposed to undergo lung biopsy with a thoracoscopic minimally invasive intervention for disseminated pulmonary lesions of various genesis. The main group (MG) included 10 patients in whom the developed software was used to determine the location points of the thoracoports. The control group (CG) consisted of 20 patients in whom diagnostic surgery was performed as per standard methods.Results. In the case of disseminated pulmonary lesions, this technology allows increasing the frequency of the presence of diagnostically significant structures in the specimen obtained by TBLB for histological examination (from 56.3 to 90.0%) and reducing the duration of diagnostic thoracoscopic minimally invasive interventions (from 39.75 to 33.50 min.).